1979
DOI: 10.1038/bjc.1979.118
|View full text |Cite
|
Sign up to set email alerts
|

Antibody-dependent and spontaneous lympholysis in urologic cancer patients

Abstract: Summary.-To evaluate cytotoxic function mediated by killer lymphocytes and macrophages in urological cancer patients, we examined antibody-dependent and spontaneous lympholysis of chicken erythrocyte target cells, which is mediated by macrophages. Our results demonstrate a discordance between cytotoxic mechanisms in cancer patients, killer-cell function being impaired whilst macrophage-mediated cytotoxicity was increased.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1982
1982
2013
2013

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 17 publications
1
2
0
Order By: Relevance
“…These responses have been reported in carcinomas of the prostate, transitional cell carcinomas of the bladder, and granular cell carcinomas of the kidney, and generally are accepted as demonstrating immunologic responsiveness by the patient toward his tumor [ll]. Ratliff et al [12] reported that in Immunologic responsiveness of patients toward urologic tumors previously has been reported by our laboratory. These studies identified elevated levels of circulating immune complexes [ 131, specific cell-mediated immunity against homologous tumor extracts [ 141, and peripheral blood leukocytic subset alterations in prostatic cancer patients [15].…”
Section: Discussionsupporting
confidence: 56%
“…These responses have been reported in carcinomas of the prostate, transitional cell carcinomas of the bladder, and granular cell carcinomas of the kidney, and generally are accepted as demonstrating immunologic responsiveness by the patient toward his tumor [ll]. Ratliff et al [12] reported that in Immunologic responsiveness of patients toward urologic tumors previously has been reported by our laboratory. These studies identified elevated levels of circulating immune complexes [ 131, specific cell-mediated immunity against homologous tumor extracts [ 141, and peripheral blood leukocytic subset alterations in prostatic cancer patients [15].…”
Section: Discussionsupporting
confidence: 56%
“…In 1979, Herberman RG et al summarised in a review article [ 38 ] that NK activity had been found to be impaired in tumour-bearing mice and patients that had large tumour loads. In later years, more reports showed that the ADCC activity of NK cells was impaired in patients with cancer, including breast [ 39 ], gastric [ 40 ], esophageal [ 41 , 42 ], and urologic cancers [ 43 ] as well as leukemia [ 44 - 46 ] and myeloma [ 47 ]. In addition, NK activity can decline with age [ 48 ], which may contribute to higher incidence of cancer developed in elderly populations.…”
Section: Discussionmentioning
confidence: 99%
“…A few years after the discovery of NK cells [21][22][23], it was found that NK cells could be impaired, observed as lower level/decreased activity in peripheral blood lymphocytes (PBL), by tumors in animals and cancer patients [24]. In later years, more reports showed that the ADCC activity of NK cells was impaired in patients with cancer [1,25,26], including head and neck [27,28], breast [29], gastric [30], esophageal [31,32], cervical [33] and urologic cancers [34] as well as leukemia [35][36][37] and myeloma [38]. In addition, NK activity could decline with age [39], which may contribute to and explain why higher incidence of cancer developed in elderly populations.…”
Section: Impairment Of Nk Cells In Cancer Patientsmentioning
confidence: 99%